DEVELOPMENT OF A COUPLE COMMUNICATION STYLE INVENTORY - Sánchez Aragón, Rozzana; Díaz- Loving, Rolando (Anales de Psicología / Annals of Psychology, 2003)
The role of communication in intimate relations has become a major area of psychological and social research in the past thirty years (e.g. Norton, 1978, Fitzpatrick, 1987, 1988; Noller, Petersen y Feeney, 2001). Within the field, special attention has been given to behavioral patterns and communication styles present during the symbolic exchange conducted by couples. In this particular paper, the styles used by Mexican couples were identified by means of ethnopsychological methodologies and compared with does described in the international literature (e.g. Satir, 1986; Miller, Nunnally y Wackman, 1976), in order to develop a universal, yet culturally sensitive measurement instrument of communication styles. Among the conceptually clear factor validated dimensions found in Mexico, an Empathic and Social Expressive, Social Affiliative, Social Self modifying, Simpatico y Social Normative, Machiavellic, Gossiping e Hurtful and an Irritant Expressive dimension appeared. Statistical and normative attributes are presented for each dimension as well as their conceptual relation with previous research and measurement instruments.